The effect of self-disclosure on mass trust through TikTok: An empirical study of short video streaming application users - Ruangkanjanases, Athapol; Sivarak, Ornlatcha; Jong, Din; Zhou, Yajun (Frontiers in Psychology, 2022)
In the short video application scenario, self-disclosure helps to establish and maintain relationships with others, and is important for the formation of mass trust. To this end, this study investigates the impact of self-disclosure on mass trust in the context of short video applications based on social exchange theory, and introduces perceived similarity to explain the specific impact mechanism while focusing on the boundary conditions of trust disposition in it. This study takes TikTok as the research object and analyzes the data obtained from the questionnaire survey. The empirical test results show that self-disclosure not only affects mass trust directly, but also indirectly through perceived similarity. In addition, a moderating effect of trust disposition on perceived similarity was found to affect mass trust. The findings of this paper contribute to an in-depth understanding of the potential intermediate mechanisms and boundary conditions of self-disclosure on mass trust, reveal the theoretical relationship between self-disclosure and mass trust, bridge the gap between previous mechanisms of mass trust influence from the perspective of empirical research, and effectively guide the management practice of short video applications.